2013
DOI: 10.1037/a0029169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal linkages among parent–child acculturation discrepancy, parenting, parent–child sense of alienation, and adolescent adjustment in Chinese immigrant families.

Abstract: Parent-child acculturation discrepancy is a risk factor in the development of children in immigrant families. Using a longitudinal sample of Chinese immigrant families, the current study examined how unsupportive parenting and parent-child sense of alienation sequentially mediate the relationship between parent-child acculturation discrepancy and child adjustment during early and middle adolescence. Acculturation discrepancy scores were created using multilevel modeling to take into account the interdependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 70 publications
3
85
1
Order By: Relevance
“…57 Crane et al found that greater differences between acculturation of parents and adolescents were associated with greater levels of depression among adolescents, 58 and Kim et al found that a discrepancy in parent-child American orientation was associated with depressive symptoms among Chinese adolescents with foreign-born parents. 59,60 …”
Section: Question 2: What Are the Unique Social Conditions That Make mentioning
confidence: 99%
“…57 Crane et al found that greater differences between acculturation of parents and adolescents were associated with greater levels of depression among adolescents, 58 and Kim et al found that a discrepancy in parent-child American orientation was associated with depressive symptoms among Chinese adolescents with foreign-born parents. 59,60 …”
Section: Question 2: What Are the Unique Social Conditions That Make mentioning
confidence: 99%
“…Prior work has highlighted the utility of examining acculturation in early adolescence: during that period of time, it has marked effects on students’ later socioemotional wellbeing and achievement (Kim, Chen, Wang, Shen, & Orozco-Lapray, 2013). It is also important to examine the extent to which early acculturation influences achievement trajectories, as academic performance is often subject to substantial changes (typically declines) during adolescence (Eccles et al, 1993; Gutman, Sameroff, & Cole, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented lower academic achievement among adolescents experiencing parent-child acculturation discrepancy, possibly due to disrupted family functioning (Kim, Chen, Wang, Shen, & Orozco-Lapray, 2013). However, there is also evidence suggesting the importance of distinguishing among different types of acculturation dissonance (Telzer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Second-generation Asian American adults may be more likely to be unhappy if they have strained social relations with their parents or have had a psychologically depressing (though not necessarily economically deprived) childhood (Kim, Chen, Wang, Shen, & Orozco-Lapray, 2013). As noted earlier, conflict between first-generation and second-generation Asian Americans is seen as being common and is often related to the high educational expectations of Asian American immigrant parents.…”
mentioning
confidence: 96%